ANXA10 induction by interaction with tumor‐associated macrophages promotes the growth of esophageal squamous cell carcinoma. Issue 3 (13th February 2019) - Kodaira, Himiko; Koma, Yu‐ichiro; Hosono, Masayoshi; Higashino, Nobuhide; Suemune, Kazuki; Nishio, Mari; Shigeoka, Manabu; Yokozaki, Hiroshi
Abstract : Tumor‐associated macrophages (TAMs) have important roles in the growth, angiogenesis and progression of various tumors. Although we have demonstrated the association of an increased number of infiltrating CD204 + TAMs with poor prognosis in esophageal squamous cell carcinomas (ESCCs), the roles of TAMs in ESCC remain unclear. Here, to study the effects of TAMs on the tumor microenvironment of ESCCs, we established a co‐culture assay using a human ESCC cell line and TAM‐like peripheral blood monocyte‐derived macrophages and performed a cDNA microarray analysis between monocultured and co‐cultured ESCC cell lines. Our qRT‐PCR confirmed that in the co‐cultured ESCC cell lines, CYP1A1, DHRS3, ANXA10, KLK6 and CYP1B1 mRNA were highly up‐regulated; AMTN and IGFL1 mRNA were down‐regulated. We observed that the high expression of a calcium‐dependent phospholipid‐binding protein ANXA10 was closely associated with the depth of invasion and high numbers of infiltrating CD68 + and CD204 + TAMs and poor disease‐free survival ( P = 0.0216). We also found ANXA10 promoted the cell growth of ESCC cell lines via the phosphorylation of Akt and Erk1/2 pathways in vitro . These results suggest that ANXA10 induced by the interaction with TAMs in the tumor microenvironment is associated with cell growth and poor prognosis in human ESCC tissues.